Turkish validity and reliability of the pound satisfaction scale in stroke patients undergoing rehabilitation - SARI, ZÜBEYİR (My University, 2024)
Purpose: This study aimed to evaluate the Turkish validity and reliability of the Pound Satisfaction Scale (PSS). Methods: For the adaptation of the PSS to Turkish (PSS-Tr), the translation and back-translation process was carried out by following the international guidelines. Confirmatory factor analysis (CFA) was performed to measure structural validity. The relationship between PSS-Tr and the Patient Satisfaction Scale in Physiotherapy (PSSP) and the SF-36 was assessed for construct validity. Convergent validity was evaluated computing by the Average Variance Extracted (AVE). Cronbach’s alpha coefficient and Composite reliability (CR) for internal consistency of the PSS-Tr and Bland- Altman plot and test-retest reliability analysis for temporal consistency were used. Results: The study included 130 stroke patients. The fit index values of the CFA showed that the structural validity of the PSS-Tr was appropriate (χ2/sd=1.779, RMSEA=0.075, GFI=0.911, AGFI=0.853, CFI=0.955, NFI=0.905). A high correlation was found between the PSS-Tr total score and the PSSP (p=0.001, r=0.672). A moderate correlation was found between the hospital satisfaction sub-dimension of PSS-Tr, and the sub-dimensions of SF-36 (p=0.001, r=0.484-0.609), while a low correlation was found between the home satisfaction sub-dimension of the PSS-Tr and the physical functioning (p=0.002, r=0.266) and physical role (p=0.035, r=0.180) sub-dimensions of SF-36. And also the PSS-Tr was found to have good internal (Cronbach alpha= 0.895, CR=0.94) and temporal consistency (ICC = 0.976). Conclusion: The Turkish version of the Pound Satisfaction Scale (PSS-Tr) is reliable and valid. The PSS-Tr may be useful for clinicians and researchers in assessing satisfaction with rehabilitation in stroke patients. Keywords: Patient Satisfaction, Rehabilitation, Stroke

Amaç: Bu çalışmada Pound Memnuniyet Ölçeği (PMÖ)’nin Türkçe geçerlilik ve güvenilirliğini araştırmak amaçlanmıştır. Yöntem: PMÖ’nün Türkçeye uyarlanması (PMÖ-Tr) için çeviri süreci uluslararası yönergelere göre yapıldı. Yapısal geçerlilik, doğrulayıcı faktör analizi (DFA) ile gerçekleştirildi. PMÖ ile Fizyoterapide Hasta Memnuniyet Ölçeği (FHMÖ) ve SF-36 ölçekleri arasındaki ilişki yapı geçerliliği açısından değerlendirildi. Yakınsak geçerlilik, Ortalama Açıklanan Varyans değerleri hesaplanarak değerlendirildi. PMÖ-Tr’nin iç tutarlılığı; Cronbach’s alpha katsayısı, birleşik güvenilirlik ve Bland Altman grafiği ile değerlendirildi. Zamansal tutarlılık ise test-tekrar test yöntemi ile değerlendirildi. Sonuçlar: Bu çalışmaya 130 inme hastası dâhil edildi. DFA kapsamındaki uyum değerlerine göre PMÖ-Tr’in yapı geçerliliği açısından uygun bulundu (χ2/sd=1,779; RMSEA=0,075; GFI=0,911, AGFI=0,853; CFI=0,955; NFI=0,905). PMÖ-Tr toplam skoru ile FHMÖ arasında güçlü bir korelasyon saptandı (p=0,001; r=0,672). SF-36’un alt boyutları ile PMÖ-Tr’in hastane memnuniyeti arasında orta düzeyde bir korelasyon saptanırken (p=0,001; r=0,484-0,609), PMÖ-Tr’in ev memnuniyeti ile SF- 36’un fiziksel fonksiyon (p=0,002; r=0,266) ve fiziksel rol güçlükleri (p=0,035; r=0,180) alt boyutları arasında zayıf bir korelasyon bulundu. Ayrıca PMÖ-Tr’nin iyi bir iç (Cronbach alpha= 0,895; CR=0,94) ve zamansal tutarlılığı (ICC= 0,976) olduğu belirlendi. Tartışma: Pound Memnuniyet Ölçeği›nin Türkçe versiyonu (PMÖ-Tr) güvenilir ve geçerlidir. PMÖ-Tr, inmeli hastalarda rehabilitasyon ile ilgili memnuniyet düzeyinin değerlendirilmesinde klinisyenler ve araştırmacılar için yararlı olabilir. Anahtar Kelimeler: Hasta Memnuniyeti, İnme, Rehabilitasyon
Rehabilitasyon hizmeti alan inmeli hastalarda pound memnuniyet ölçeği Türkçe geçerlilik ve güvenilirliği
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Rehabilitasyon; Ortopedi; Clinical Medicine (Med); Clinical Medicine; Orthopedics; Ortopedi ve Spor Hekimliği; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Orthopedics and Sports Medicine; Physical Therapy, Sports Therapy and Rehabilitation; Patient Satisfaction; Stroke; Hasta Memnuniyeti; İnme; Rehabilitation